The Gastroprotective Effect of Vitex pubescens Leaf Extract against Ethanol-Provoked Gastric Mucosal Damage in Sprague-Dawley Rats - Saeed AL-Wajeeh, Nahla (PLoS One, 2016)
Vitex pubescens is a Malaysian therapeutic plant employed in traditional drug to remedy a variety of disorders. The purpose of this research is to assess the gastroprotective efficiency of V. pubescens leaves against ethanol-induced gastric hemorrhagic laceration in rats. Animals were randomly allocated into seven groups and pre-treated, separately, with 10% Tween 20 (normal and ulcer control groups), 20 mg/kg omeprazole (reference group), and 62.5, 125, 250, and 500 mg/kg of V. pubescens extract (experimental groups). All animals were sacrificed after another hour. Histological evaluation of the ulcer control group revealed significant injury to the gastric mucosa with edema and leucocyte infiltration of the submucosal layer. PAS staining, showed remarkably intense magenta color, remarkable increase of HSP70 and decrease of Bax proteins in rats pre-treated with plant extracts compared to the ulcer control group. Gastric homogenates revealed a remarkable increase in endogenous antioxidant enzyme activities (CAT, SOD, GSH) and a decrease in the lipid peroxidation level (MDA) in animals pre-treated with V. pubescens extract compared with the ulcer control group. The gastroprotective activity of this plant might be related to increased antioxidant enzymes and decrease lipid peroxidation upsurge of HSP70 and reduced expression of Bax proteins